Long Non-Coding RNAs: Novel Players in Regulation of Immune Response Upon Herpesvirus Infection - Ahmed, Waqas; Liu, Zheng-Fei (Frontiers in Immunology, 2018)
Herpesviruses have developed a variety of sophisticated immune evasion strategies to establish lifelong latent infection, including the use of long non-coding RNAs (lncRNAs). In this review, we summarize the lncRNA action modes, i.e., RNA–protein, RNA–RNA, and RNA–DNA interactions, involved in regulating important aspects of immunity by controlling gene expression at various stages. Upon herpesvirus infection, host lncRNAs such as NEAT1, NRAV, and BIC have been functionally characterized as negative or positive antiviral regulators in the immune response. Herpesviruses have also evolved multiple strategies to modulate the host immune response using lncRNAs such as LAT, β 2.7 RNA, 5 kb and 7.2 kb lncRNAs, EBER, BARTs, PAN, and HSURs. We discuss the various mechanisms of immune-related lncRNAs, and their diversified and important functions in the modulation of innate and adaptive immunity upon herpesvirus infection as well as in host-pathogen interactions, which will facilitate our understanding of rational design of novel strategies to combat herpesvirus infection.